ヘリウム マイクロハ ユウドウ プラズマ ハッコウ ブンセキホウ (He-MIP-AES) ニヨル ショウワキチ タイキチュウ エアロゾル ノ トクセイカ - 浅野, 比; アサノ, ヒトシ; 青山, 朋樹; アオヤマ, トモキ; 菊地, 正; キクチ, タダシ; 和田, 誠; ワダ, マコト; Asano, Hitoshi; Aoyama, Tomoki; Kikuchi, Tadashi; Wada, Makoto (2010)
P(論文) 本研究では南極昭和基地大気中のエアロゾルに関し,個々の粒子に関する粒径分布,成分組成,化学状態の情報が同時に得られるヘリウムマイクロ波誘導プラズマ発光分析装置(He-MIP-AES)を現地に持ち込み分析を行った.その結果,Na,Mg,Caの元素を含む粒子数が多く,海塩起源の粒子を多く含んでいることが明らかとなった.また,Si,Feなどが検出されていることから土壌起源粒子が含まれていることが明らかとなった.風速が強く,降雪があるときは,土壌成分の巻き上げや,雪氷からの海塩成分の飛散等により粒子数が増加する傾向にあった. Atmospheric aerosols at Syowa Station, Antarctica were characterized by helium microwave induced plasma atomic emission spectrometry (He-MIP-AES). The He-MIP-AES can be considered as a suitable method for the characterization of the atmospheric particulate matter since measurements of grain size distribution, elemental analysis for each particle, and chemical state analysis can be available simultaneously. Previous characterization methods such as XRF, PIXE and ICP-MS cannot provide in situ analysis and they need a long time to measure of the distribution of the particle diameter and elemental analysis of each particle. The particle samples in the atmosphere were collected on the membrane lter at Syowa Station in Antarctica. The obtained particles were analyzed by the He-MIP-AES (HORIBA, particle analyzer DP-1000). Elemental analysis, chemical state analysis, and grain diameter distribution analysis were performed. The collected particles mainly contain sea salt (Na, Mg and Ca) and soil origin constituents (Si and Fe). The counts of each element increase under blizzard and strong wind condition. departmental bulletin paper